Electrodiagnostic approach in entrapment neuropathies of the median and ulnar nerves - Galamb, Ana Maria (Pak J Med Sci, 2015)
OBJECTIVE: The present study’s aim was to analyze the late responses’ parameters in order to determine the utility of each one. METHODS: The study, conducted on a total of 325 patients with entrapment neuropathy of the median nerve and 36 with entrapment neuropathy of the ulnar nerve, included the bilateral evaluation of the median and the ulnar nerve and analysis of 20 F-wave and 4 A-wave parameters. RESULTS: The authors emphasize the necessity of bilateral examination and that of examining the ipsilateral ulnar/median nerve, such as to calculate the difference in F-wave average latency of the median/ulnar and the ipsilateral ulnar/median nerve. This was the most sensitive parameter studied, altered in more than 70% of cases, significantly in more cases than when using only the M-wave distal latency. Also there was a statistically significant correlation between patient age and F-wave latency. CONCLUSIONS: The completed research yielded the recommendation for F-wave parameter studies to include the difference in F-wave average latency of the median/ulnar and the ipsilateral ulnar/median nerve. This parameter was also included in the composite score, along with the recommendations of the American Academy of Emergency Medicine (AAEM).